Biological Activities of Water-Soluble and Сu2+ Salts of Gossypol Derivatives Metallocomplexes - Khakberdiyev Shukhrat Mahramovich, Azizova Safina Isroiljon qizi, Mamatova Farangiz Qodir qizi, Rabbimova Marjona Ulug‘bek qizi (Scientific Trends, 2023)
Synthesized derivatives of gossypol, supramolecular complexes with monoammonium salt of glycyrrhizic acid, the metal complexes of Schiff bases of gossypol and salts of Cu. Analyze their IR, UV spectra and studied their effect on the number of macrophages within 24 and 48 hours in peritoneal fluid of thymus and spleen of intact mice.
Keywords: Gossypol, amino compound, Schiff's base, spectrum, polyphenol, triterpene, aldehyde, cotton plant, naphthalene, MSGA.